Association of radiological type of dural tail sign in contrast MRI with histopathological grading of intracranial meningiomas - Saiful Islam, Muhammad; Ansari, Ayub; Razib, K. Olinur; Ahmmed, Tayeb; Haque Jui, Mahmuda; Rahim, M. Abdur; Mostafa, M. Abu Hena; Islam, Kazi Saiful; Bari, M. Sazzadul (International Journal of Research in Medical Sciences, 2024)
Background: In neurosurgical practice meningiomas are one of the commonest intracranial tumors to seek surgical intervention which is classified into 3 histological grades and 15 subtypes according to the 2016 WHO classification of tumors of the CNS. The aim of this study was to evaluate the association between radiological type of dural tail sign in contrast MRI with histopathological grading of intracranial meningiomas. Methods: This was a cross sectional interventional study carried out in the Department of Neurosurgery, Bangabandhu Sheikh Mujib Medical University, Dhaka, Dhaka Medical College Hospital and National Institute of Neuroscience Hospital including 35 patients of intracranial meningiomas who fulfilled the selection criteria were enrolled in this study. Results: This study included 35 cases of intracranial meningiomas. There were 22 individuals (62.9%) in the 28-47 age group. The mean±standard deviation (SD) age of the participants was 45.97±9.56 years. There were 9 male participants (25.7%) and 26 female participants (74.3%) with ratio 1:3. We see that parasagittal location (50%) and sphenoid wing (33.3%) were more prevalent in grade II. We found significant distribution of the types of DTS among the histological grades of meningioma. The nodular cases (6,100%) were all grade II type. Mixed type was the most prevalent type among grade I. Conclusions: There is association of radiological type of dural tail sign in contrast MRI with histopathological grading of intracranial meningiomas and may be used as a good tools for forecasting tumor type and prognosis.